Cosmic Ray Mediated Thermal Fronts in the Warm-hot Circumgalactic Medium - Hanjue Zhu; Ellen G. Zweibel; Nickolay Y. Gnedin (The Astrophysical Journal, 2025)
We investigate the 1D plane-parallel front connecting the warm (10 ^4 K) and hot (10 ^6 K) phases of the circumgalactic medium (CGM), focusing on the influence of cosmic rays (CRs) in shaping these transition layers. We find that cosmic rays dictate the thermal balance while other fluxes (thermal conduction, radiative cooling, and gas flow) adjust to compensate. We compute column densities and ratios for the transition-temperature ions Si iv , C iv , O vi , and N v , and compare them with observational data. While most models struggle to simultaneously reproduce the observed Si iv /C iv and C iv /O vi ratios, a subset with intermediate magnetic field strength (e.g., B = 20 μ G) shows overlap with the data, although we make no claims for their uniqueness. These discrepancies suggest that the models perform better at reproducing higher-temperature ions but underestimate the contribution from cooler, photoionized regions. Compared to models without CRs, CR-mediated fronts in sufficiently strong magnetic fields produce broader transition layers and higher ion ratios, indicating that CRs can significantly alter the thermal and ionization structure of the CGM. Our results suggest that CR heating may help explain some observed ion columns under specific conditions, though additional physics may be needed for full agreement with observations.